2020
DOI: 10.1097/bot.0000000000001712
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Cage Fixation for Proximal Humerus Fractures Has Low Reoperation Rates at 1 Year: Results of a Multicenter Study

Abstract: Objectives: To determine reoperation rates after treatment of a proximal humerus fracture with cage fixation. Design: Retrospective case series. Setting: Eleven U.S. hospitals. Patients: Fifty-two patients undergoing surgical treatment of proximal humerus fractures. Intervention: Open reduction and internal fixation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The proximal humerus cage, consisting of a fixed angle expandable nitinol cage incorporating locked fixation, has been one modality of supplemental fixation used to reduce fixation failure. 38 In a multicenter study by Goodnough et al, 39 the use of the proximal humerus cage demonstrated an overall complication rate of 19.1%, with a 1-year revision surgery rate of 7.7%, which the authors noted is less than that typically seen with conventional locked plating. In a recent study by Cui et al, 40 23 patients were treated with proximal humerus locking plates in addition to a spine cage and compared with 39 patients treated with a locking plate only.…”
Section: Tips To Optimize Resultsmentioning
confidence: 96%
“…The proximal humerus cage, consisting of a fixed angle expandable nitinol cage incorporating locked fixation, has been one modality of supplemental fixation used to reduce fixation failure. 38 In a multicenter study by Goodnough et al, 39 the use of the proximal humerus cage demonstrated an overall complication rate of 19.1%, with a 1-year revision surgery rate of 7.7%, which the authors noted is less than that typically seen with conventional locked plating. In a recent study by Cui et al, 40 23 patients were treated with proximal humerus locking plates in addition to a spine cage and compared with 39 patients treated with a locking plate only.…”
Section: Tips To Optimize Resultsmentioning
confidence: 96%
“…However, the biomechanical study did not show significant differences comparing with the conventional locking plate [ 25 ]. Clinical studies have used titanium mesh or intramedullary cages to enhance the stability of plate fixation, and encouraging results have been achieved at 1-year follow-up [ 26 , 27 ]. However, fundamental technological innovations developed specifically for complex PHF with osteoporosis have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biomechanical study did not show signi cant differences comparing with the conventional locking plate [25]. Clinical studies have used titanium mesh or intramedullary cages to enhance the stability of plate xation, and encouraging results have been achieved at 1-year follow-up [26,27]. However, fundamental technological innovations developed speci cally for complex PHF with osteoporosis have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%